Experience with feeding jejunostomy. - Ahmed, Ahmed S. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Enteral nutrition is a widely used, standard-of-care technique for nutrition support in critically ill and trauma patients. Objective: to determine the role of feeding jejunostomy as a safe way for enteral nutrition in patients who meet the criteria for its use. Method: prospective, comparative study done in the 3rd. surgical unit at Baghdad Teaching Hospital from 1st.of January 2003 till 1st. of April 2009, of 230 patients who fit the criteria for feeding jejunostomy insertion. The patients were divided into 2 groups (those with feeding jejunostomy 122 patients (53%) and without feeding jejunostomy 108 patients (47%)). We follow up these patients using the particular parameters. Results: feeding jejunostomy was performed in 122 patients (53%), 68% of feeding jejunostomy was performed in urgent procedures, pancreaticoduodenal injuries was the most common indication. The BMI was noticed to be either increased in 48 patients (39.34%) or stabilized in 70 patients (57.37%) with feeding jejunostomy, while the lymphocytes count was either increased in 64 patients (52.45%) or remain within normal range in 56 patients (45.9%) with feeding jejunostomy, while serum protein level showed no decrease in any patients with feeding jejunostomy. Diarrhea was the most common complication observed in 14 patients (11.5%) with feeding jejunostomy. Conclusion: Feeding jejunostomy is an effective and safe way of delivering nutrition postoperatively. It leads to increase or stabilize BMI, lymphocytes count and serum protein level, although it produced GI complications which are generally mild and resolve quickly with non-invasive treatment.